2020
DOI: 10.1159/000507117
|View full text |Cite|
|
Sign up to set email alerts
|

Histone Deacetylases Take Center Stage on Regulation of Podocyte Function

Abstract: Background: Podocytes (highly specialized and terminally differentiated epithelial cells) are integral components of the glomerular filtration barrier that are vulnerable to a variety of injuries and, as a result, they undergo a series of changes ranging from hypertrophy to detachment and apoptosis. Podocyte injury is a major determinant in proteinuric kidney disease and identification of potential therapeutic targets for preventing podocyte injury has clinical importance. Although numerous studies have achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 62 publications
(93 reference statements)
0
2
0
Order By: Relevance
“…Paecilomyces cicadae-fermented Radix astragali can enhance the autophagy of podocytes induced by high glucose, enhance cell viability, and reduce apoptosis [25]. Histone deacetylase protects podocytes from damage by regulating inflammation, autophagy, and insulin resistance [26]. Hepatocyte growth factor regulates the PI3K/Akt-GSK3 sh-TFEB axis and protects diabetic nephropathy through the podocyte autophagy-lysosome pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…Paecilomyces cicadae-fermented Radix astragali can enhance the autophagy of podocytes induced by high glucose, enhance cell viability, and reduce apoptosis [25]. Histone deacetylase protects podocytes from damage by regulating inflammation, autophagy, and insulin resistance [26]. Hepatocyte growth factor regulates the PI3K/Akt-GSK3 sh-TFEB axis and protects diabetic nephropathy through the podocyte autophagy-lysosome pathway [27].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients with NS need to conceive daily treatment with corticosteroids until complete remission of proteinuria ( 16 ), side effects of corticosteroids are concerned, which promote us to explore potential drugs for alternative therapeutic intervention. HDAC inhibitors exhibited beneficial impacts against podocyte injury and proteinuria ( 17 ). HDAC IIa composes of HDAC4, HDAC5, HDAC7, and HDAC9, numbers of studies demonstrated HDAC IIa inhibition as an alternative approach to avoid the progression of various diseases, examples like breast tumors ( 18 ), pancreatic cancer ( 19 ), multiple myeloma ( 20 ), and type 2 diabetes ( 21 ).…”
Section: Discussionmentioning
confidence: 99%